Bullying prevention model through character education in early childhood education institutions in Malang City - Siti Mahmudah; Nurul Zuriah; Endang Poerwanti (Research and Development in Education (RaDEn), 2025)
Bullying, once perceived as a phenomenon confined to adolescence, is increasingly recognized in early childhood education. Although frequently overlooked or rationalized as playful interaction, behaviors such as name-calling, pushing, toy-snatching, or social exclusion represent forms of bullying that can disrupt children’s social, emotional, and moral development. This study aims to design a bullying prevention model through character education in Early Childhood Education (ECE) institutions located in Blimbing District, Malang City, Indonesia. A qualitative multi-site approach was employed, involving observations, interviews, and documentation in three institutions: TK Muslimat NU 14, TK Al Hadi Kids Campus, and TK ABA 12. Data analysis used the Miles et al model, covering reduction, display, and conclusion drawing. The findings revealed that bullying in ECE typically manifests in verbal (mockery, nicknames), physical (pushing, snatching toys), and social (exclusion from play) forms. Teachers and schools applied three major strategies: responsive (immediate intervention and dialogue), reflective (morning circle discussions and value reflection), and participatory (collaborative play and social responsibilities). These strategies align with the dimensions of the Profil Pelajar Pancasila—piety, mutual cooperation, critical reasoning, independence, and noble character. Based on these insights, the study proposes a four-pillar Bullying Prevention Model: positive habituation, reflective dialogue, collaborative play, and school–parent partnership. This model offers a holistic framework for building safe, inclusive, and character-based learning environments in ECE.